A NOVEL APPROACH TO EDUCATING ENGINEERS: LEARNING IN AN INVERTED CLASSROOM THROUGH PROBLEMS DESIGNED BY ENGINEERING PROFESSIONALS - SHUMAN, Teodora Rutar (Journal of Applied Engineering Science, 2016)
This paper presents a novel approach to educating engineers by using an inverted classroom (IC) to facilitate learning through in-class solving of multi-faceted problems designed by engineering professionals. The objective of this approach is to develop an instructional framework that promotes self-directed learning and enhances problem-solving skills in undergraduate engineering students without sacrificing knowledge of fundamental engineering principles. In this framework, material traditionally covered in a lecture format is moved outside of class time, developed for an on-line format, and made available in an online learning management system. In-class time is used to solve engineering problems in teams and under guidance of an instructor. The problems are co-developed with practicing engineers from aerospace, medical device, HVAC and process industries. The framework was implemented in a Heat Transfer course. Students taught using the new framework showed improvement in self-directed learning and problem-solving skills over students taught in a traditional setting without losing basic skills.